Deficiency is consent in the library service: Do professionals realize it? - Lozano, Roser (Anuario ThinkEPI, 2016)
This reflection focuses on the role of the public library in providing leadership to the social construction of cultural needs and values and offering services beyond the concrete demands of the users, and on how ignorance of the library´s potentialities limits the demands made on the public library. The need for a coherent public library project is defended as essential to obtaining the cultural leadership of our community.
Keywords: Public library; Consent deficiency; Cultural needs; Cultural values; Project; Demand